Impact of Fiscal Policy Instruments’ Dynamics on Resource Sustainability in Nigeria - A. I., Ochalibe; C. U., Okoye; A. A., Enete (International Journal of Environment, Agriculture and Biotechnology, 2019)
This research examined the impact of fiscal policy instruments on agricultural resources sustainability in Nigeria for the period 1980-2018. Specifically the study examined the causal relationship between fiscal policy instruments and resource sustainability; analyzed the instantaneous and compound growth rate of government expenditure, debt policy instruments and agricultural resources sustainability and; examined the impact of government expenditure and debt policy instrument on resource sustainability. Data were obtained from Central Bank of Nigeria (CBN) Statistics Data Base: and Food and Agriculture Organization Statistical data (FAOSTATS). From the findings, there exist a unidirectional relationship (P<0.05) from government expenditure and debt to resource sustainability index. Government expenditure and debt instruments had instantaneous and compound growth rate (P<0.05) of 7.62%, 7.92% and 1.23% and 1.24% respectively. The instantaneous growth rate for forest resources (P<0.05), arable land (P<0.05) and human capital (P<0.05) were -1.57%, 0.33% and -1.93% with a compound rate of growth of -1.58%, 0.34% and -1.93%, -1.95% respectively. Government expenditure policy instruments yielded significantly (P<0.05) positive impacts of 0.37% while increased debt profile significantly (P<0.05) decreases sustainability index by -0.27%. Thus, fiscal policy instruments dynamics is essential for the attainment of inter-temporal efficiency of resources, hence sustainability. It was recommended that non- sustainable activities such as land degradation, deforestation and human capital depletion driven by unfavorable policies needs to be reappraised.